SMOKING AND TREATMENT WITH ACUPUNCTURE HEADSET – CASES STUDY OF CLINICAL (Fiep Bulletin - online, 2013)
Smoking is currently the subject of universal interest being considered by the World Health Organization (WHO) the leading cause of preventable death worldwide. Acupuncture therapy is a specialty recognized by the World Health Organize since 1976 that uses the Auricular Acupuncture as therapeutic resource to stimulate certain points which are located in the ear, to rebalance the body. This study aims to evaluate improvements in reducing the consumption of cigarettes in smokers as well as analyze optimization of quality of life and well being of volunteers searched. We evaluated and treated five volunteers between 35 and 54 years with chief complaint of smoking in the town of Balneário Camboriú / SC. Anamnesis was conducted with a questionnaire to detect emotional problems, primary and secondary complaints that may be involved with smoking. At the test was conducted Fagerström to analyze the degree of dependence on nicotine in the body. The volunteers were subjected to the application of needles semipermanent of 1.5 mm, according to the complaints and perceived changes in the questionnaire. Specific points were used to treat smoking them being the Shen Men, Kidney, the sympathetic nervous system, Vice bilateral, Lung (2X), Diaphagm (in case of cough), external nose, mouth (if associated with hunger), Intestine, Liver, Anxiety 1 and 2, Liver yang 1 and 2, Tension and Heart. The reduction of cigarettes through Auriculotherapy occurred in all volunteers. The effectiveness of auricular therapy for reduction of cigarettes to smokers was 100% (all volunteers reduced the number of cigarettes daily). As for the secondary benefits of this treatment there was improvement in the respiratory system (cough, coryza, hoarseness, respiratory system), digestive (gastritis, heartburn), emotional (irritability, anxiety).